Gold(I)‐Catalyzed endo‐Selective Intramolecular α‐Alkenylation of β‐Yne‐Furans: Synthesis of Seven‐Membered‐Ring‐Fused Furans and DFT Calculations1. Issue 52 (19th November 2013) - Dong, Zhe; Liu, Cheng‐Hang; Wang, Yi; Lin, Mu; Yu, Zhi‐Xiang
<x xml:space="preserve">Abstract</x> Alkenylation of furans: An efficient gold‐catalyzed endo‐selective intramolecular α‐alkenylation of β‐alkyne‐substituted furans has been developed to synthesize challenging seven‐membered‐ring‐fused furans in good to excellent yields. Preliminary DFT calculations have been carried out to understand the experimentally observed regioselectivity. DME=1, 2‐dimethoxyethane, Ts=p‐toluenesulfonyl.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>